EFFECT OF RADIO WAVES ON THE HUMAN BODY - Erkaboyeva Laylo Shermat qizi; Suyunova Sevinch Mingboy qizi; Karimova Sevara Abror kizi; Qurbonov Jamshid Muyiddinovich (Web of Journals Publishing, 2025)
Technological advances of mankind through the development of electrical and communication technologies have led to the exposure of artificial electromagnetic fields. Technological growth is expected to continue; therefore, the amount of EMF exposure will continue to grow steadily. In particular, the time of use of smart phones is increasing, which has become a necessity for modern people. When considering the area where the mobile phone is used, interest in social anxiety and the effects on the cranial nervous system increases. Scientific research on the mechanism of biological effects is also required. Furthermore, RF-EMF acts as a source of stress in living beings.
Keywords: Homeostasis, thermoregulation, electromagnetic, extrapolation, restrictions, controlled environment.